HUBUNGAN ANTARA DUKUNGAN SOSIAL KELUARGA DENGAN KEPATUHAN INTAKE DIIT CAIRAN PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA DI RUANG MALAHAYATI RSUD Dr. SAIFUL ANWAR MALANG (PROFESSIONAL HEALTH JOURNAL, 2023)
Long-term hemodialysis lowers a patient's zest for life, which may have an impact on how well they follow their dietary guidelines. Dietary noncompliance is a major issue, particularly for people receiving hemodialysis. The client's quality of life may be negatively impacted by non-compliance, and rising medical expenses may have an adverse effect on hemodialysis patient compliance. The purpose of this study is to ascertain how family social support and fluid intake compliance relate to each other in patients with chronic renal failure receiving hemodialysis at Dr. Saiful Anwar Regional Hospital in Malang. Quantitative descriptive research is the kind that this study is doing. 110 patients with chronic kidney failure who received hemodialysis in the Malahayati ward at RSUD Dr. Saiful Anwar Malang, were included in the study's population as of March 2023. Purposive sampling was utilized in the sampling process to yield 52 respondents. A questionnaire is used in this study as the measurement method. The Spearman Rank correlation test is the data test that is employed. According to the Spearman Rank correlation test results, there is a connection between patients with chronic renal failure receiving hemodialysis at RSUD Dr. Saiful Anwar Malang and their compliance with fluid consumption (p value <0.05). It is intended that Dr. Saiful Anwar Hospital will enhance its offerings and educate families about the support networks available to patients as they receive hemodialysis treatment and manage their fluid intake.